GAMBARAN KESEHATAN MENTAL REMAJA YANG TERPAPAR KDRT - Larashati, Lelita; Naomi Soetikno (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2023)
Domestic violence is known as the cause of psychological disorders in victims, perpetrator and their children. Literature studies shown that negative effects of domestic violence is found as a negative influence in the development of childhood and adolescence. However, most studies had focus on victims and perpetrator with minimal data of psychological disorders in adolescence who got exposed to domestic violence. Results of this paper showed that 50 participants aged 15-19 shows indication of depression, anxiety and/or stress disorders. Anxiety disorder is found in most of participants.